Improving Student Learning Outcomes Using the Problem Based Learning (PBL) Model Assisted by QR Code Card Media in the Ipas Subject for Grade V Students at Elementary School - Faizal Tri Haryanto; Ria Apriani; Denny Hotnida Tampubolon (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2024)
This study aims to enhance students' cognitive learning outcomes using the Problem-Based Learning model assisted by QR Code Card media. The research method employed by the researchers is Classroom Action Research (CAR) with four main stages: (1) planning, (2) action, (3) observation, and (4) reflection. The research was conducted in grade V of SDN 37 Bengkulu City with 25 student participants. Data collection techniques included observation and tests. The improvement in cognitive learning outcomes of grade V students at SDN 37 Bengkulu City is evident from the pre-cycle results, where only 10 out of 25 students (40%) achieved mastery. In cycle I, the student’s learning outcomes increased to 72% mastery; by cycle II, 92% of students achieved mastery. This research met the success indicator set by the researchers, which was 80%, with the final result in cycle II being 92%. From this research, it can be concluded that applying the Problem-Based Learning model assisted by QR Code Card media can improve the cognitive learning outcomes of grade V students at SDN 37 Bengkulu City.